Números complexos, projeção estereográfica e projeção de mercator: uma proposta de motivação ao aluno do colégio naval a respeito do curso de hidrografia - Souza, Shalon Gonçalves de (2022)
Colégio Naval (CN) is the only military education institution in Brazil whose main mission is the intellectual and physical preparation of young people aiming to enter the Naval Academy (EN). The EN, in turn, trains Officers for the initial positions in the careers of the Navy Corps, Marine Corps and Navy Quartermasters. It would be useful and convenient, both for young graduates from the NC and for the Brazilian Navy, to identify those with a certain aptitude and present them, while still at the CN, with the career possibilities that are most likely to reconcile the needs of the Force with the students' innate propensities. Thus, this Dissertation aims to offer a proposal to identify NC students who have a predilection for Mathematics and suggest a career course option as an Officer of the Navy Corps. Hence the motivation for the theme “Complex Numbers, Stereographic Projection and Mercator Projection: a motivational proposal for the Colégio Naval student regarding the Hydrography Course”. To reach the objective, after pointing out in the Introduction the relevance of Complex Numbers and the controversial decision of no longer charging certain subjects as required skills in the National High School Examination, we move on to Chapter 2, with a brief history of Complex Numbers, ending with the necessary theoretical foundation. In chapter 3, the Stereographic and Mercator Projections are presented, with some characteristics of each one, highlighting them as a link between marine themes and Mathematics, to then present the Hydrography Course for Officers. In Chapter 4, the Final Considerations are summarized, concluding with the suggestion of the Hydrography Course for Officers as a career alternative for CN students who wish to extend their Mathematics experience beyond the Brazilian Navy school benches.